DEVELOPING MACROMEDIA FLASH TEACHING MATERIAL IN THE TOPIC OF NEGOTIATING TEXT FOR MUHAMMADIYAH VOCATIONAL SCHOOL IN MAGELANG - Wati, Nur Rahma (Universitas Ahmad Dahlan, 2019)
The purpose of this study is to develop Macromedia Flash teaching materials to increase student learning outcomes and to determine the feasibility of Macromedia Flash-based teaching materials. This research is research and development (R & D) using the 4D development model. This study involved subjects namely students of Grade X of Muhammadiyah Mungkid Vocational School and Salaman Muhammadiyah Vocational School. Data analysis uses quantitative data analysis. The analysis used was an independent sample t-test using SPSS version 17. The results of the development produced a product in the form of Macromedia Flash-based learning media on the subject of negotiation text for learning Bahasa Indonesia. The results of the research suggest that there are differences in the average score of student learning outcomes before and after using Macromedia Flash media. The percentage of students reaching the passing grade of 75 before using Macromedia Flash or conventional media is 9% and after using Macromedia Flash media to 68.3%. The result of calculated-t value is 10.3 while the t-table is 1.657. The t-test analysis proves that Macromedia Flash learning media is suitable for Bahasa Indonesia learning, especially on the subject of negotiation text. Moreover, the learning is more effective than using conventional learning media.